Endogenous electric field-driven neuro-immuno-regulatory scaffold for effective diabetic wound healing - Zhiqing Liu; Tianlong Wang; Jinhui Zhao; Lei Zhang; Yiping Luo; Yixing Chen; Xinhui Wu; Yaqi Liu; Aihemaitijiang Aierken; Dilixiati Duolikun; Hui Jiang; Xinyu Zhao; et al. (Bioactive Materials)
The pathological microenvironment in diabetic wounds is delineated by heightened inflammatory responses and persistent proinflammatory macrophage activity, which significantly hinders the wound healing process. Exogenous electrical stimulation (ES), by modulating the electric field distribution in wounds, has shown significant potential in treating inflammatory wounds. However, this approach relies on additional power sources and complex circuit designs. Here, a bionic neuro-immuno-regulatory (BNIR) system was proposed for reshaping the endogenous electric fields (EFs) through collecting ion flow. The BNIR system comprises microporous structure scaffolds and nanosheets, enabling swift biofluid collection and electrical signal transmission, with the ability to promote cell proliferation and migration and exhibit antioxidant properties. More importantly, the BNIR system induced the transition of M1 macrophages to M2 macrophages through neuro-immuno-regulatory. In diabetic rat skin wounds, the BNIR system significantly enhanced healing by simultaneously neuro-immuno-regulatory, promoting angiogenesis, scavenging ROS, and facilitating tissue remodeling. This work aims to advance the development of a bionic system for electrosensitive tissue repair.